PENGARUH ISI PESAN STOP BODY SHAMING PADA SIKAP FOLLOWERS TERHADAP BODY SHAMING - Diajeng Maharani; Yani Hendrayani; Vina Mahdalena (Jurnal Pustaka Komunikasi, 2020)
This study discusses the effect of stop body shaming message content on followers attitude againts body shaming. This study aims to determine the magnitude of the effect of the contents of the stop body shaming message on followers attitude againts body shaming. The model used in this study is a persuasive instrumental of model. The method used is quantitative. Data collection is done by distributing questionnaires. The population in this study is the Instagram account followers @kemenpppa, for samples using the Yamane formula which is then obtained by 100 respondents. The sampling technique used in this study was purposive sampling technique. The results showed that the results of the correlation test variable X (the contents of the body shaming message) to the variable Y (body shaming attitude) amounted to 0.752. Based on the calculation of the coefficient of determination results obtained the influence of variable X on variable Y by 56.5%. T test results obtained t count t table that is t count 11.295 1.661, it can be concluded that H0 is rejected and Ha is accepted. The conclusion from the study is that there is a strong influence between the contents of the stop body shaming message on Instagram @kemenpppa on followers attitude againts body shaming.